Synthesis and characterization of biodegradable elastomers for soft tissue engineering - Lee, Lan Yin. (2009)
Herein, the synthesis and evaluation of a new group of biodegradable elastomeric polyesters, poly(1, 12-dodecandiol-co-malic acid) is performed. The main objectives of this project are to design a malic acid-based aliphatic polyester material with desirable modulus, elasticity and degradation rate. Two-dimensional poly(1, 12-dodecandiol-co-malic acid) scaffolds were prepared by reacting malic acid with different diol ratios under nitrogen flow to form pre-polymers. Pre-polymers were then post-polymerized at 140oC and 160oC under vacuum (30 kPa) for various days. 8 scaffolds with different acid to diol ratios were synthesized and post-polymerization under different conditions and then characterized. All scaffolds demonstrated good thermal stability. Seven out of eight materials passed the in vitro cytotoxicity test with the Young’s modulus ranged from 1.13±0.65MPa to 4.04±0.78MPa. Elongation was as high as 1070.48±265.14%. The mechanical properties and degradation rate could be controlled by choosing different acid to diol ratios as well as by modulating the post-polymerization conditions. In addition, this study would like to propose PDDM1-1,21,0 and PDDM1-2,36,0 for further investigation as they showed desirable thermal and mechanical properties, degradation rate and excellent results for cell growth.